Nature strange and beautiful : how living beings evolved and made the earth a home - Leigh, Egbert Giles, Jr., 1940- (Yale University Press, 2019)
A beautifully written exploration of how cooperation shaped life on earth, from its single-celled beginnings to complex human societies In this rich, wide-ranging, beautifully illustrated volume, Egbert Leigh explores the results of billions of years of evolution at work. Leigh, who has spent five decades on Panama's Barro Colorado Island reflecting on the organization of various amazingly diverse tropical ecosystems, now shows how selection on "selfish genes" gives rise to complex modes of cooperation and interdependence. With the help of such artists as the celebrated nature photographer Christian Ziegler, natural history illustrator Deborah Miriam Kaspari, and Damond Kyllo, Leigh explains basic concepts of evolutionary biology, ranging from life's single-celled beginnings to the complex societies humans have formed today. The book covers a range of topics, focusing on adaptation, competition, mutualism, heredity, natural selection, sexual selection, genetics, and language. Leigh's reflections on evolution, competition, and cooperation show how the natural world becomes even more beautiful when viewed in the light of evolution